2014
DOI: 10.1140/epjd/e2014-40787-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of optical lattice potentials on the vortices in rotating dipolar Bose-Einstein condensates

Abstract: Abstract. We study the interplay of dipole-dipole interaction and optical lattice (OL) potential of varying depths on the formation and dynamics of vortices in rotating dipolar Bose-Einstein condensates. By numerically solving the time-dependent quasi-two dimensional Gross-Pitaevskii equation, we analyse the consequence of dipole-dipole interaction on vortex nucleation, vortex structure, critical rotation frequency and number of vortices for a range of OL depths. Rapid creation of vortices has been observed du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 64 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Numerical results of the dipolar GPE in the quasi-twodimensional regime [198,199] show that, for an adiabatic introduction of the rotation frequency, the strength of the dipolar interaction influences the rotation frequency at which vortices are admitted into the condensate. In agreement with analysis presented above, it is also found that as the dipolar interaction is increased the rotation frequency required to nucleate vortices is reduced.…”
Section: Does the Final State Of The System Contain Vortices?mentioning
confidence: 99%
“…Numerical results of the dipolar GPE in the quasi-twodimensional regime [198,199] show that, for an adiabatic introduction of the rotation frequency, the strength of the dipolar interaction influences the rotation frequency at which vortices are admitted into the condensate. In agreement with analysis presented above, it is also found that as the dipolar interaction is increased the rotation frequency required to nucleate vortices is reduced.…”
Section: Does the Final State Of The System Contain Vortices?mentioning
confidence: 99%
“…These studies revealed that the rotational properties of dipolar BECs are strongly influenced by the harmonic trap aspect ratio, DDI strength, contact interaction (CI) strength and relative strengths between DDI and CI [20,21]. Square and triangular vortex lattice structures have been predicted in dipolar BECs loaded in optical lattice potentials [22]. The stability of dipolar BEC is strongly dependent on the trap geometry and dipolar interaction strength.…”
Section: Introductionmentioning
confidence: 99%
“…The standard model also find a lot of new applications presented in Refs. [21]- [34]. Speaking about application of the standard model of dipolar BECs we should mention that we explicitly apply the full potential of the electric dipole interaction (see formula (5) below, or papers [8], [9], [11]), whereas the standard model contains the shorted potential with no delta function term.…”
Section: Introductionmentioning
confidence: 99%